Provincial and District Extension Agents in Mekong Delta, Vietnam: Perceived Differences in Extension Skills and Performance - Thach, Le Ngoc; Ismail, Maimunah; Uli, Jegak; Idris, Khairuddin (2007)
Extension agents are professionals who link development agencies and community in the process of technology transfer and helping the productivity of agriculture. There are two types of extension agents, namely those at provincial and district levels. This paper examines differences in extension skills and performance between provincial and district extension agents. A survey research was conducted in seven provinces of Mekong Delta, Vietnam to a sample of 312 respondents at provincial and district levels. The study reveals four types of skills that are different between the two groups of extension professionals. Recommendations for human resource development are discussed.